2019
DOI: 10.1016/j.ccell.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of RNA Splicing Catalysis through Inhibition of Protein Arginine Methylation

Abstract: Highlights d Inhibition of SDMA or ADMA preferentially kills splicing factor (SF)-mutant cells d Combined inhibition of PRMT5 and type I PRMTs has synergistic effects d RNA-binding proteins are the most enriched cellular substrates of PRMTs d Inhibition of RNA splicing underlies the cytotoxic effects of PRMT inhibition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
235
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(254 citation statements)
references
References 90 publications
9
235
0
Order By: Relevance
“…To characterize PRMT enzymes' substrate motifs, a variety of targeted enzymatic and computational approaches have been used (Wooderchak et al 2008;Gathiaka et al 2016;Gayatri et al 2016). Finally, others have tested the proteomic and transcriptomic consequences of inhibition of various PRMTs Eram et al 2016;Fong et al 2019;Musiani et al 2019;Radzisheuskaya et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize PRMT enzymes' substrate motifs, a variety of targeted enzymatic and computational approaches have been used (Wooderchak et al 2008;Gathiaka et al 2016;Gayatri et al 2016). Finally, others have tested the proteomic and transcriptomic consequences of inhibition of various PRMTs Eram et al 2016;Fong et al 2019;Musiani et al 2019;Radzisheuskaya et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PTMScan-previously developed to immunoprecipitate post-translationally modified peptides after lysate protease cleavage (Stokes et al 2012)-was used in HEK293 cells to identify thousands of PRMT-regulated Rme1 sites (Larsen et al 2016) and to identify PRMT1 substrates in Toxoplasma (Yakubu et al 2017). Others have used PTMScan with SILAC to identify sites of all three methylarginine states, mostly found to be enriched in RNA-binding proteins and regulating splicing (Fong et al 2019;Musiani et al 2019;Radzisheuskaya et al 2019). Middle-down proteomics coupled with electron-transfer dissociation (ETD) was used to specifically identify arginine methylation in arginine-and serine-rich domains in RNA-binding proteins (Kundinger et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several complementary reports demonstrated that combining PRMT1 inhibitors with PRMT5 inhibitors resulted in synergistic anti-tumor activity (Fedoriw, et al 2019;Fong, et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of splicing factors by kinases of the SRPK and CLK families control their enzymatic activity and subcellular localization 61 and AML cells are sensitive to pharmacological inhibition of these kinases 62 . Many RNA binding proteins are also methylated by the PRMT family of protein arginine methyltransferases and PRMT inhibition kills leukemic cells 63 . Furthermore, splicing alterations due to epigenetic or chromatin changes due to somatic mutations 44,64 or possibly as a consequence of aging 65 have also been recently reported.…”
Section: Discussionmentioning
confidence: 99%